The Impact Of Emotıonal Intellıgence And Famıly Envıronment On Socıalızatıon Abılıtıes Of Upper-Grade Sd Muhammadıyah Pk Baturan Students - Nugraha, Nurcahyati; Sukartono (Elementary Teacher Education Program, Majalengka University, 2025)
This research aims to: 1) determine the influence of emotional intelligence on the socialization abilities of upper-grade elementary school students; 2) examine the impact of family environment on the socialization abilities of upper-grade elementary school students; and 3) investigate the combined effect of emotional intelligence and family environment on the socialization abilities of upper-grade elementary school students. The study employed a quantitative ex-post facto approach, conducted with 48 fourth and fifth-grade students at SD Muhammadiyah Special Program Baturan, selected through proportionate stratified random sampling. Data was collected using questionnaires with good reliability for each variable (emotional intelligence 0.851, family environment 0.845, and socialization ability 0.887). The research findings indicate that: 1) emotional intelligence significantly influences students' socialization ability, with tcount = 6.096 > ttable = 2.015 and Sig. = 0.000; 2) family environment significantly affects students' socialization ability, with tcount = 2.545 > ttable = 2.015 and Sig. = 0.014; and 3) emotional intelligence and family environment collectively have a significant impact on students' socialization ability, with Fcount = 63.259 > Ftable = 3.21 and Sig. = 0.000. The coefficient of determination (R2) of 0.738 indicates that 73.8% of the variation in students' socialization ability can be explained by emotional intelligence and family environment, while 26.2% is influenced by other factors outside the scope of this study.